An evaluation of Caritas Masvingo in creating resilient communities in Masvingo Bikita district ward 12 - Mbedzi, Gibson (Midlands State University, 2017)
The study seeks to find out if Caritas Masvingo is creating resilient communities in Bikita ward 12 that is if Caritas is providing communities with resources such that communities would be able to sustain themselves in terms of food, income generation, living a good standard of life . The study looks at the challenges faced by Bikita ward 12 communities even before Caritas Masvingo intervened in ward 12 which include shortages of water, food insecurity, and lack of income generation activities, livestock diseases, unemployment and droughts. The study looks at the impacts these challenges has had on the communities in ward 12. The study goes on to look at the various programmes such as dam construction, Isal and the goat project Caritas is putting in place in ward 12 to address these challenges, the measures put in place to ensure sustainability of these programmes and how Caritas is working with government departments such as VET,LPD and Agritex in ward 12. A conclusion with the final assessment and some recommendations was done by the researcher basing on the findings of the research study.